PROFIL ERUPSI OBAT DI RSUD DR. PIRNGADI KOTA MEDAN TAHUN 2015 – 2017 - DIZA TANZIRA; DIAN ERISYAWANTY BATUBARA (JURNAL ILMIAH MAKSITEK, 2020)
Indiscriminate use of drugs, the entry of new drugs almost every day on the market, and the lack of habits to report theoccurrence of drug eruption reactions, has resulted in a high incidence of drug eruption reactions occurring. Due to the lackof the latest data regarding the epidemiology of drug eruptions, this has led to need for more research. To determine theprofile of drug eruption at the regional hospital of Dr. Pirngadi in Medan City in the period of 2015-2017. Descriptive studywith cross-sectional approach from secondary data based on the medical records of in-patients and out-patients treated inthe regional hospital of Dr. Pirngadi in Medan City in the period of 2015-2017. During the period of January 2015 - December2017, there were 87 cases of drug eruption. The age group of 45-64 years (36,8%) was the commonest age group. Theincidence of drug eruption by sex, women (54,0%) is more frequent than men (46,0%). Allergic history is almost entirely notlisted on medical records (94,5%). The most frequently associated disorders was non-infectious disease (37,9%). Themaculopapular rash type is the commonest clinical manifestation of drug eruption (37,9%). The most suspected drugs thatcause the eruption was antibiotic (48,3%). The most widely used treatments were combination of corticosteroid andantihistamine (33,3%). In this study, the age group of 45-64 years was the commonest age group and women is morefrequent than men to develop drug eruption. The maculopapular rash type is the commonest clinical manifestation of drugeruption.